The Influence of Flipped Classroom on Student Engagement Considering Growth Mindset in Secondary Schools in Indonesia - Nita Rosmala Dewi; Istiarsyah Istiarsyah (The Eastasouth Journal of Learning and Educations, 2026)
Student engagement is a crucial factor in determining the effectiveness of the learning process in secondary education. However, traditional teaching methods often limit students’ active participation in classroom activities. Therefore, innovative learning approaches such as the flipped classroom have gained attention as a strategy to enhance student engagement. This study aims to examine the effect of the flipped classroom on student engagement while considering the role of growth mindset among Indonesian high school students. The study employed a quantitative research design involving 150 students as respondents. Data were collected using a structured questionnaire measured with a five-point Likert scale. The collected data were analyzed using SPSS version 25 through descriptive statistics, validity and reliability testing, and multiple linear regression analysis. The results indicate that the flipped classroom has a positive and significant effect on student engagement (β = 0.421, p < 0.05). In addition, growth mindset also significantly influences student engagement (β = 0.356, p < 0.05). The simultaneous analysis shows that both variables significantly contribute to student engagement with a coefficient of determination (R²) of 0.507, indicating that 50.7% of the variation in student engagement can be explained by the flipped classroom and growth mindset variables. These findings suggest that integrating flipped classroom learning strategies with the development of a growth mindset can enhance students’ participation, motivation, and involvement in the learning process. The study provides practical implications for educators to adopt more interactive instructional approaches while fostering positive learning beliefs among students in Indonesian high schools.